Proses berpikir kritis siswa ditinjau dari kemampuan awal matematis - Fitria, Nury Ainun; Sabandar, Jozua; Kadarisma, Gida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This study aims to observe the process of students' critical mathematic alabilities in the context of their initial mathematical knowledge. The research utilized a qualitative approach with a descriptive method. The research was conducted at SMP Negeri 7 Cimahi with a sample of 34 students from class VIII-E. The results show that students with good initial mathematical abilities demonstrate better critical thinking skills compared to students with lower initial abilities. High-category students are able to provide detailed answers, supported by appropriate evidence and conclusions, despite minor errors. Medium-category students can answer correctly and provide sufficient reasons and evidence, although sometimes imprecise. Low-category students can provide correct answers but lack supporting evidence and reasons. These findings indicate a positive correlation between initial mathematical abilities and critical mathematical thinking skills. Therefore, improving students' critical mathematical thinking skills requires efforts to enhance their initial mathematical abilities through adaptive and effective teaching methods.